ADAMTS-7 forms a positive feedback loop with TNF-α in the pathogenesis of osteoarthritis. Issue 8 (8th August 2013) - Lai, Yongjie; Bai, Xiaohui; Zhao, Yunpeng; Tian, Qingyun; Liu, Ben; Lin, Edward A; Chen, Yuqing; Lee, Brendan; Appleton, C Thomas; Beier, Frank; Yu, Xiu-Ping; Liu, Chuan-ju
Abstract : Objective: To examine the expression of ADAMTS-7 during the progression of osteoarthritis (OA), defining its role in the pathogenesis of OA, and elucidating the molecular events involved. Methods: ADAMTS-7 expression in cartilage of a rat OA model was assayed using immunohistochemistry. Cartilage-specific ADAMTS-7 transgenic mice and ADAMTS-7 small interfering (si)RNA knockdown mice were generated and used to analyse OA progression in both spontaneous and surgically induced OA models. Cartilage degradation and OA was evaluated using Safranin-O staining, immunohistochemistry, ELISA and western blotting. In addition, mRNA expression of tumour necrosis factor (TNF)-α and metalloproteinases known to be involved in cartilage degeneration in OA was analysed. Furthermore, the transactivation of ADAMTS-7 by TNF-α and its downstream NF-κB signalling was measured using reporter gene assay. Results: ADAMTS-7 expression was elevated during disease progression in the surgically induced rat OA model. Targeted overexpression of ADAMTS-7 in chondrocytes led to chondrodysplasia characterised by short-limbed dwarfism and a delay in endochondral ossification in 'young mice' and a spontaneous OA-like phenotype in 'aged' mice. In addition, overexpression of ADAMTS-7 led to exaggerated breakdown of cartilage and accelerated OA progression, while knockdown of ADAMTS-7 attenuated degradation of cartilage matrix and protected against OA development, in surgically induced OA models. ADAMTS-7 upregulated TNF-α and metalloproteinases associated with OA; in addition, TNF-α induced ADAMTS-7 through NF-κB signalling. Conclusions: ADAMTS-7 and TNF-α form a positive feedback loop in the regulation of cartilage degradation and OA progression, making them potential molecular targets for prevention and treatment of joint degenerative diseases, including OA.